1988
DOI: 10.1159/000205593
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal and Oligoclonal Immunoglobulins in the Serum of Patients with B-Chronic Lymphocytic Leukemia

Abstract: The incidence of monoclonal and oligoclonal immunoglobulins (paraproteins) was determined in serum samples of 45 chronic lymphocytic leukemia (B-CLL) patients using the high-resolution agarose gel electrophoresis technique combined with immunofixation. Paraproteins were identified in 25 of the 45 patients tested. Twelve paraproteins were monoclonal and 13 oligoclonal. IgG k and/or λ immunoglobulin isotypes were found in 17/25 of these patients. No correlation of the lymphocyte cell morphology and the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The patient had normal serum immunoglobulin levels and a normal pattern of the albumin, alpha, beta and gamma globulins fractions. The serum protein electrophoresis analysis of our patient showed, as previously reported for some CLL patients, [3][4][5] a small monoclonal component (0.5 g/dL). Immunoglobulin levels, albumin and globulin s fractions, as well as the monoclonal component remained stable in all the peripheral blood analysis performed since the diagnosis until the present.…”
supporting
confidence: 87%
“…The patient had normal serum immunoglobulin levels and a normal pattern of the albumin, alpha, beta and gamma globulins fractions. The serum protein electrophoresis analysis of our patient showed, as previously reported for some CLL patients, [3][4][5] a small monoclonal component (0.5 g/dL). Immunoglobulin levels, albumin and globulin s fractions, as well as the monoclonal component remained stable in all the peripheral blood analysis performed since the diagnosis until the present.…”
supporting
confidence: 87%
“…Both family history and personal history of autoimmune disease were independent predictors of risk of MGUS [45]. A population-based study had already shown the association of autoimmune conditions and the risk of The association of MGUS and well-differentiated B-cell NHL is a well-known phenomenon [33][34][35][36]. Already in 1978, Lennert et al reported that approximately 20% of all patients with lymphoplasmacytic lymphoma have serum monoclonal immunoglobulin [37].…”
Section: Discussionmentioning
confidence: 99%
“…But, for CLL patients, bone marrow aspirates or biopsies are only indicated in cases of cytopenia or to assess complete remission after therapy, as recommended by the guidelines of the international workshop on CLL (Hallek et al, 2018). Furthermore, although IgM paraprotein is frequent in CLL, lymphoplasmacytic differentiation remains rare (Rizzo et al, 2015) and the IgM peak might not be due to the CLL clone (Pangalis et al, 1988). Among MZL, bone marrow involvement mainly concerns patients with splenic or nodal MZL (Ponzoni et al, 2012; and is uncommon in extranodal cases (EMZL) (Starr, Caimi, Fu, Massoud, Meyerson, Hsi, Mansur, Cherian, Singh, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%